Legal Protection For Buyers In Trading Land Rights Exercised In Front of The Village Head (The Practice oof Buying and Selling Land Rights Is Not Done Before PPAT In Plana Village Somagede District Banyumas Regency). - yulia yulia widiastuti (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2020)
The sale and sale of land rights must be done in the presence of PPAT as proof that there has been a sale and purchase of a land right and then PPAT makes a Deed of Sale and Then followed by registration at the local Land Office following the location of the land. But the fact that until now there is still a sale of land rights done in the presence of the Village Head, as happened in Plana Village Somagede District Banyumas Regency. The point raised in this study is why are the people of Plana Village Somagede sub-district still there who trade land rights, not before the authorized officials, namely PPAT? and what is the legal protection for buyers of land rights that are not done in the presence of authorized officials, namely PPAT? This research uses sociological juridical approach methods, primary data, and secondary data obtained and then analyzed based on legal norms and theories namely legal protection and legal effectiveness. From the results of the research and concluded, then the Village Head must dare to refuse to buy and sell land rights in front of him and the local government policy must impose strict sanctions on the Village Head who violated it, the socialization of the Banyumas district land office must be carried out regularly so that the people trade rights on the land following the prevailing regulations and for the villagers of Plana who have been able to trade rights on the land in front of the Village Head to immediately transition the rights to the land following Article 37 paragraph (1) or paragraph (2) of Government Regulation No. 24/1997 on Land Registration.Keywords: Buy and Sell, Village Head, PPAT